2021
DOI: 10.3390/biomed1010006
|View full text |Cite
|
Sign up to set email alerts
|

Guillain–Barré Syndrome in COVID-19—The Potential Role of NCAM-1 and Immunotherapy

Abstract: Coronavirus disease 2019 (COVID-19) interacts with the nervous system directly and indirectly by affecting the activation of the immune system. Guillain–Barré syndrome (GBS) is triggered by an inappropriate immune system activation that overlaps with the neurotoxic mechanism of an invading pathogen. Here, we discuss the complexity of an abnormal immune system response leading to the generation of autoimmunity in the setting of acute viral infection. A 67-year-old male patient with COVID-19 developed a sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…Finally, NCAM-1, an adhesion molecule involved in neural cell adhesion and synaptic plasticity, has also been related to neuroinflammation. The expression of NCAM-1 has been found dysregulated during the course of COVID-19 neuroinfection and a potential role in Guillain-Barre syndrome has been reported [104,105]. In our study, increased serum NCAM-1 concentration in WNND patients suggests a peripheral neuronal effect that can occur during WNV infection.…”
Section: Discussionsupporting
confidence: 57%
“…Finally, NCAM-1, an adhesion molecule involved in neural cell adhesion and synaptic plasticity, has also been related to neuroinflammation. The expression of NCAM-1 has been found dysregulated during the course of COVID-19 neuroinfection and a potential role in Guillain-Barre syndrome has been reported [104,105]. In our study, increased serum NCAM-1 concentration in WNND patients suggests a peripheral neuronal effect that can occur during WNV infection.…”
Section: Discussionsupporting
confidence: 57%
“…Our analyses identify four genetic variants (in/near TAS2R1 , ZBTB16 , LINC01320 , and NCAM1 ) (Jansen et al, 2022; Laudanski et al, 2021; Mastropasqua et al, 2021; Morsy, 2020; Shelton et al, 2021; Watanabe et al, 2020) that have been reported with COVID‐19 outcomes.…”
Section: Resultsmentioning
confidence: 83%
“…The encoded protein is involved in cell‐to‐cell and cell‐to‐matrix interactions during development and differentiation (Gao et al, 2010). As a binding partner of spike protein, a recent study suggests that a viral mutation at site S2 of the spike protein may increase proteolytic activity and membrane fusion, causing SARS‐CoV‐2 to be more infectious (Hahn et al, 2021); additionally, previous investigations have revealed that there might exist molecular mimicry between NCAM1 and the COVID‐19 envelope protein (Laudanski et al, 2021; Morsy, 2020). Furthermore, in the same super variant, we observe that the SNP rs73000932 is considered as an intronic variant for gene ZBTB16 (also referred to as promyelocytic leukemia zinc finger).…”
Section: Resultsmentioning
confidence: 99%
“…Our analyses identify 4 genetic variants (in/near TAS2R1, ZBTB16, LINC01320 and NCAM1) [11,[27][28][29][30][31] that have been reported with COVID-19 outcomes.…”
Section: Supervariantsmentioning
confidence: 83%
“…The encoded protein is involved in cell-to-cell and cell-to-matrix interactions during development and differentiation [32]. As a binding partner of spike protein, previous investigations have revealed that there might exist molecular mimicry between NCAM1 and the COVID-19 envelope protein [29, 30]. Furthermore, in the same super variant, we observe that the SNP rs73000932 is considered as an intronic variant for gene ZBTB16 (also referred to as promyelocytic leukemia zinc finger).…”
Section: Resultsmentioning
confidence: 99%